Aviation and Climate Change - Abeyratne, Ruwantissa. author. aut Link
X, 159 p.
Keywords: The book addresses the most critical issue faced by aviation and climate change: namely the development of a market based measure to control aircraft engine emissions. It discusses the current market economic trends as they impact to aviation and suggests steps and measures to be taken in the development of a workable MBM. ICAO has three years to come up with such an MBM on a global scale and this book will spur discussions on how to achieve this objective.